A gut instinct for childhood leukemia prevention: microbiome-targeting recommendations aimed at parents and caregivers - Kameri, Ersen; Jepsen, Vera Helena; Stachura, Pawel; Rüchel, Nadine; Bhave, Rigveda; Benitez, Leticia; Crispi, Fatima; Gratacos, Eduard; Dragano, Nico; Janssen, Stefan; Borkhardt, Arndt; Pandyra, Aleksandra; et al. (Frontiers in Public Health, 2025)
Childhood leukemia accounts for 30% of all pediatric cancer cases with acute lymphoblastic leukemia (ALL) being the most common subtype. Involvement of the gut microbiome in ALL development has recently garnered interest due to an increasing recognition of the key contribution the microbiome plays in maintaining the immune system's homeostatic balance. Commensal gut microbiota provide a first line of defense against different pathogens and gut microbiome immaturity has been implicated in ALL pathogenesis. Several environmental factors such as nutrition, mode of delivery, breastfeeding and, early social or livestock contacts are known to alter the composition of the gut microbiota. Variations in these factors influence the risk of childhood leukemia onset. This review aims to elucidate the risk factors influencing microbial composition in the context of childhood ALL. The link between gut microbiome diversity and childhood ALL offers the opportunity to develop risk-reducing strategies that can be communicated to a broad target population of (future) parents and caregivers for childhood leukemia prevention. Here, we summarize evidence on how promoting a diverse gut microbiome in newborns through simple measures such as increasing social contacts early in life may decrease the risk of developing ALL in these children later on.